The Effect of Organisational Power on Structural Empowerment and Awareness of Ability Levels Among a Sample of Nurses - Rabhi Mokhtar; Thamri Ahlam; Djoual Mohammed Said; Harizi Rima Affaf (Economics and Business)
The paper assesses the effect of organisational power on the structural empowerment of hospital nurses. The study also explores the degree to which nurses are able to take more responsibility in their work. Data were taken from 100 nurses of the Algerian public hospital. The model was tested by partial least squares path modelling. The results showed that organisational power positively affected structural empowerment. In addition, nurses have the ability to take on more responsibilities at work. Increasing nurses’ structural empowerment is an essential outcome. Therefore, it is necessary to move away from extreme centralization and try to share information, support, and experience with nurses, especially at public hospitals. Heads of nursing departments must share experience and information and delegate powers to nurses to enhance the effectiveness of their performance, especially in response to emergencies, and create the appropriate environment to enhance the empowerment of nurses.